Flipped classroom video-based instruction to foster critical reasoning and learning independence in elementary learners - Waty, Citra Kumala; Buchori, Achmad; Asrofah, Asrofah (Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyse the effect of the application of the flipped classroom learning model integrated with video learning on lower-class elementary school students, which is still limited to an empirical study. Previous research generally focused on the application of flipped classrooms at the secondary and tertiary education levels, while this study adapted the model to elementary school grade III science learning by considering the characteristics of students' cognitive development through the use of simple and contextual learning videos. This study uses a quantitative method with an experimental design. The research subjects were selected based on the inclusion and exclusion criteria that had been set. Data was collected through a critical reasoning ability test and a learning independence questionnaire, then analysed using the N-Gain Score, the Independent Sample T-Test, and a simple linear regression test. The results showed that the improvement in students' ability in the experimental class (N-Gain 78.34%) was higher than that of the control class (41.94%), with an average score of 86.32 and 68.22, respectively. The regression test showed that the learning model had a significant effect on students' critical reasoning skills and learning independence. These findings suggest that video-assisted flipped classrooms are effectively applied to science learning in lower-class elementary schools.